Synthesis of bovine hydroxyapatite-iron composite via dry mechanochemical process for biodegradable bone scaffolds - Nordin, JA (2013)
Hydroxyapatite (HAp) is widely used in orthopedic and dental surgeries [1]. This study aims to synthesize a Fe-reinforced natural HAp composite via dry mechanochemical process without chemical addition. An improvement to the mechanical strength and cytocompatibility is expected with the presence of Fe ions in the HAp structure.